HUBUNGAN DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN KEMAMPUAN BERSOSIALISASI PADA SISWA SMK NEGERI 3 MEDAN - Sri Wahyuni, Nini (JURNAL DIVERSITA, 2016)
This study aims to determine the relationship between social support peers in social skills to students of SMK Negeri 3 Medan. The subjects were students of SMK Negeri 3 Medan which numbered 60 people. Measuring instrument used is a Likert scale consisting of 36 items sociability (Î± = 0.897) and 46 items of peer social support (Î± = 0,929). Data analysis using techniques r Product Moment. Berdasdarkan data analysis, found that the hypothesis proposed in this study received, that there is a relationship between social support peers in social skills to students of SMK Negeri 3 Medan. This is evidenced by the value or coefficient of correlation ((r xy = 0.942, p = 0.000; p <0.05). Furthermore, seen from the calculation of hypothetical mean and the empirical mean and standard deviation is known that social support peers in social skills to students of SMK Negeri 3 field are low, where the average value of the empirical lower than the average value of the hypothetical.